Snow-covered surface variability and DEM generation using aerial photogrammetry in Mount Odin, Canada - Najibi, Nasser; Arabsheibani, Reza (Geodesy and Cartography, 2013)
Seasonal snow-covered surface has a critical role in global water resource supplement especially providing fresh water for humankind and flora's consumptions as well as local underground water storages. The in situ measurements of seasonal snow-covered variability are extensively prodigal and costly particularly in existence of severe climate conditions such as high latitude regions and polar areas. It is therefore necessary to apply remote sensing techniques and observations to estimate accurately the snowpack melting and accumulation for different seasons. In this paper, we estimate snow-covered surface variability for four different seasons of year in Mount Odin, Canada using aerial photos. In order to do this, firstly Digital Elevation Model (DEM) with respect to Earth Gravitational Model 1996 (EGM96) for each flight mission of A, B, C and D from these aerial photos by applying Bundle Adjustment (BA) triangulation is being generated precisely. Moreover, the displacement of each two DEMs is computing in order to determine snow-covered surface variability between each two flight missions. The results demonstrate that flight mission C has the highest elevation topographically compare to the missions A, B and D while mission C was planned in February 2011 in existence of vast snow throughout Mount Odin area as well as mission C's DEM which has higher elevation values than the others. The proposed methodology and problem solution and the case study information with the details of each flight mission are discussed in expatiation.